ANALISIS KINERJA DAN PROSPEK SWASEMBADA KEDELAI DI INDONESIA - Muhammad Firdaus (RELASI : JURNAL EKONOMI, 2012)
This study aims: (1) To identify trends harvest area, production, and productivity of soybean in Indonesia. (2) To determine the tendency of soybean demand in Indonesia. This study uses secondary data (1995-2011). The data were obtained from the Deptan, BPS, and FAOSTAT. Data analysis using the least squares method . The results showed that: (1) The harvested area and soybean production in Indonesia tend to decrease, but the productivity tends to increase. (2) The level of soy consumption will still higher than the level of soybean production, so without the right policies, soybean self-sufficiency target will not be achieved.